The Effect of Land Characteristics on Agricultural Productivity Using Multiple Linear Regression Method in Madiun Regency, East Java - Istifaroh Elya Pratiwi (EDP Sciences, 2021)
Agriculture is an important sector to support national food availability. Soil and climatic conditions in Indonesia are very suitable for agriculture. However, the land characteristics in each region are different, Especially in Madiun Regency, where this study is conducted. This study aims to determine what commodities are suitable for the characteristics of the land based on land suitability and how land characteristics influence agricultural productivity. The data used in this research is secondary data. Determination of agricultural commodities is carried out by cross-checking between land characteristics and guidelines for agricultural commodity land requirements. There are six types of agricultural commodities that are suitable for land characteristics in Madiun Regency. The effect of land characteristics consisting of several parameters on agricultural productivity was sought using multiple linear regression methods. The processing results are known that 8 variables of land characteristics significantly affect agricultural productivity by 93%. The independent variables were tested using the Simultaneous F-Test and were known to have a simultaneous (together) effect on agricultural productivity. In addition, a Partial T-Test was conducted, and it was found that there were only two variables that had a partial effect, namely the soil CEC characteristics and the sand characteristics.